Killers of the flower moon [videorecording (DVD)] - DiCaprio, Leonardo; De Niro, Robert; Plemons, Jesse, 1988-; Gladstone, Lily; Grann, David (Criterion collection, 2026)
An epic elegy of greed, betrayal, and murder, Martin Scorsese's masterly adaptation of David Grann's true-crime best seller unfolds in 1920s Oklahoma, where the discovery of oil brings extraordinary wealth to the Osage people. Into their world comes ne'er-do-well army veteran Ernest Burkhart, who joins his duplicitous uncle in a horrifying scheme to rob the Osage of their money and land. Lily Gladstone charges the film with her transcendent performance as Burkhart's Osage wife, Mollie Kyle, gradually awakening to the evil that surrounds her.